Pyrolysis characteristics of mallee biomass - Hasan, MD Mahmudul (Curtin University, 2015)
The overall technical feasibility of a novel grinding pyrolysis technology has been demonstrated at a pilot plant scale. The pyrolysis behaviour of mallee biomass was investigated in this pilot plant under a wide range of experimental conditions. Further experiments were also carried out by pyrolysing single mallee wood cylinders in a fluidised sand bed. The data from this study provide essential information for the commercialisation of this novel grinding pyrolysis technology.